2012
DOI: 10.5194/bg-9-3739-2012
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing greenhouse gas fluxes across nine European peatlands and shrublands – responses to climatic and environmental changes

Abstract: In this study, we compare annual fluxes of methane (CH<sub>4</sub>), nitrous oxide (N<sub>2</sub>O) and soil respiratory carbon dioxide (CO<sub>2</sub>) measured at nine European peatlands (<i>n</i> = 4) and shrublands (<i>n</i> = 5). The sites range from northern Sweden to Spain, covering a span in mean annual air temperature from 0 to 16 °C, and in annual precipitation from 300 to 1300 mm yr<sup>−1</sup>. The effects of climate change, i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 70 publications
2
27
1
Order By: Relevance
“…2), possibly mainly from AR. As in other wooded peatlands 7,8,11 , drainage did not raise SR ( Supplementary Fig. 2), although more reactive nitrogen was available in drained sites compared with restored sites (Supplementary Table 3).…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…2), possibly mainly from AR. As in other wooded peatlands 7,8,11 , drainage did not raise SR ( Supplementary Fig. 2), although more reactive nitrogen was available in drained sites compared with restored sites (Supplementary Table 3).…”
mentioning
confidence: 49%
“…These hydrologic shifts often threaten carbon stores, changing peatlands from a carbon sink to a carbon source by increasing decomposition 2,3,[14][15][16] ; concomitantly, the crucial peat-forming Sphagnum mosses are replaced by shrubs/trees 2,10,12 with possibly substantial feedbacks on climate change 6,10 . However, recent evidence showed that in some peatlands drought had little impact or even decreased CO 2 emission and increased carbon accumulation [7][8][9][10][11][17][18][19] (Supplementary Table 1). These contrasting results raise uncertainty on the future fate of peat carbon and question the conventional theory that anoxia is the key to sustaining peat carbon.…”
mentioning
confidence: 99%
“…For example, a recent analysis of CH 4 flux measurements made across different soil types and land-uses in the UK showed that AMo CH 4 fluxes (37 µg m −2 h −1 ) were at the top end of the range of CH 4 fluxes reported for mineral soils (17 to 40 µg m −2 h −1 ), rather than peatlands (17 to 1580 µg m −2 h −1 ) (Levy et al, 2012). The largest CH 4 fluxes in that analysis were recorded from the deep peats in the flow country (Loch More) (peat depth = 4 m), but also from a lowland raised bog, Whim Bog within 2 km of AMo (peat depth = 6 m) (Levy et al, 2012;Carter et al, 2012). Methane fluxes at Loch More and Whim Bog were at least 50 times larger than those at AMo, and were similar to those measured in northern Finland (Drewer et al, 2010;Lohila et al, 2011).…”
Section: Methane and Nitrous Oxide Fluxesmentioning
confidence: 91%
“…Roulet et al (2007) for a range of northern Ontario peatlands. In an extensive synthesis of data for a broad range of European peatlands Carter et al (2012) also recorded annual CH 4 flux to be between 0.5 to 6.8 gCH 4 -C m -2 y -1 . Estimated night CO 2 -C losses from the S1-Bog are over 40 times higher than the CH 4 -C losses, suggesting a minimal role for CH 4 -C efflux in the overall NEE from the bog.…”
Section: Annual C Effluxmentioning
confidence: 99%